Centralized vehicle leasing in humanitarian fleet management: the UNHCR case. Issue 3 (7th December 2015) - Kunz, Nathan; Van Wassenhove, Luk N.; McConnell, Rob; Hov, Ketil
Abstract : Purpose: – Fleet management is a key function in humanitarian organizations, but is not always recognized as such. This results in poor performance and negative impacts on the organization. The purpose of this paper is to demonstrates how the UN High Commissioner for Refugees (UNHCR) managed to substantially improve its fleet management through the introduction of an Internal Leasing Program (ILP), in which headquarters procures vehicles and leases them to field offices. Design/methodology/approach: – This paper develops a framework for fleet management based on a longitudinal case study with UNHCR. It compares fleet performance indicators before and after implementation of an ILP. Findings: – At UNHCR, vehicle procurement was driven by availability of funding. Fleet management was highly decentralized and field offices had limited awareness of its importance. These systems and behaviors led to major challenges for the organization. The introduction of the ILP positively impacted fleet management at UNHCR by reducing fleet size, average age of fleet and procurement costs. Practical implications: – This paper provides fleet managers with a tool for analyzing their fleet. The frameworks and actions described in this paper contain practical recommendations for achieving a well-performing fleet. Originality/value: – This paper is the first to analyze fleet management before and after introduction of an ILP. It describes the benefits of this model based on empirical data, and develops frameworks to be used by researchers and practitioners.